2016
DOI: 10.1136/bcr-2016-216122
|View full text |Cite
|
Sign up to set email alerts
|

Morel-Lavallee seroma (post-traumatic pseudocyst) of back: a rarity with management conundrum

Abstract: Morel-Lavallee seroma (MLS) or post-traumatic pseudocyst is a soft tissue seroma developing due to closed degloving injury by a shearing force that causes separation of subcutaneous fatty layer from the deeper muscular fascia resulting in collection of fluid in the created space. Presentation is usually fluctuant swelling following history of injury. More frequently described in orthopaedic literature, it occurs more commonly over gluteal and trochanteric regions, knee and flanks with occurrence over back, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Acute small lesions are often treated conservatively with compression bandages, non-steroidal anti-inflammatory medication and physiotherapy. 5 Whilst chronic lesions have traditionally been treated with surgical debridement, 6 it has subsequently been found that smaller lesions may be amenable to percutaneous aspiration and compression treatment. 7 Surgery is more invasive and carries risks of viability to the adjacent superficial soft tissue, and it has been suggested that aspiration allows for shorter recovery times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute small lesions are often treated conservatively with compression bandages, non-steroidal anti-inflammatory medication and physiotherapy. 5 Whilst chronic lesions have traditionally been treated with surgical debridement, 6 it has subsequently been found that smaller lesions may be amenable to percutaneous aspiration and compression treatment. 7 Surgery is more invasive and carries risks of viability to the adjacent superficial soft tissue, and it has been suggested that aspiration allows for shorter recovery times.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, percutaneous treatment by combined aspiration and sclerotherapy has proved an effective minimally invasive alternative, which has been utilized for hip and knee lesions 8 as well as in a case study of a lesion extending over the thoracic and lumbar spine. 5 General complications for aspiration and sclerotherapy are difficult to define given that a heterogenous group of different sclerosants have been trialled, such as talc, ethanol, fibrin glue and tetracycline antibiotics. 9 With talc sclerodesis, a case series has demonstrated pain during the procedure, as well as a case of infection and subsequent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Morel-Lavallee lesion (MLL) is a possible diagnosis for the case at hand. Morel-Lavallee lesion also known as closed degloving injury or post traumatic pseudocyst was described initially in 1853 by Dr. Maurice Morel-Lavallee [ 11 , 12 ]. It usually arises secondary to trauma or shearing force which subsequently results in the separation of subcutaneous tissue from the deep muscle fascia.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the creation of a space which can be filled by blood, lymph, or necrotic fat [ 13 ]. While the majority of these lesions arise directly after injury, approximately one third of lesions might present gradually months to years after the inciting event [ 11 , 12 ]. When left untreated, these gradually growing lesions might often be confused with a soft tissue tumor [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation